Experimental and natural host specificity of Loma salmonae (Microsporidia) - Shaw, Ross W.; Kent, Michael L.; Brown, A. M.; Whipps, C. M.; Adamson, Martin L. (My University, 2000)
The microsporidian Loma salmonae (Putz, Hoffman & Dunbar, 1965) Morrison & Sprague, 1981 has caused significant gill disease in Pacific salmon Oncorhynchus spp. Host specificity of the parasite was examined experimentally by per os challenge of selected salmonids and non-salmonids with infective chinook salmon O. tshawytscha gill material. Pink Oncorhynchus gorbuscha and chum salmon O. keta, brown Salmo trutta and brook trout Salvelinus fontinalis, and chinook salmon (controls) were positive, whereas Atlantic salmon Salmo salar and Arctic char Salvelinus alpinus were negative. In addition, no non-salmonids were susceptible to experimental exposure. Wild Pacific salmon species in British Columbia, Canada, were examined for L. salmonae during their freshwater life history stages (smolts, prespawning, spawning). All stages were infected, although infections in smolts were only detectable using a L. salmonae-specific PCR test. Many previous Loma spp. described from Oncorhychus spp. are likely L. salmonae based on host, parasite morphology, and site of infection.
Keywords: Loma salmonae; Microsporidia; transmission; host specificity